The Effectiveness of Consuming Watermelon in Reducing Hypertension in Pregnant Women at Nurlina Independent Practice Midwife, Kampung Baru Village, Bukit Kapur District, Dumai City Year 2023 - Marlina, Mila (Cattleya Darmaya Fortuna, 2024)
This study aims to evaluate the effectiveness of watermelon consumption in reducing hypertension in pregnant women at Nurlina Independent Practice Midwife, Kampung Baru, Bukit Kapur, Dumai City. Hypertension in pregnant women is a significant health problem, which can have a negative impact on maternal and fetal health. The research design used was pre-experimental with a one-group pre-post test approach, involving 20 pregnant women respondents who experienced hypertension. Data were collected through blood pressure measurements before and after the intervention of watermelon consumption for 7 days, with data analysis using paired t-test statistical test to determine significant differences between pre-test and post-test values. The results showed that there was a significant reduction in blood pressure after watermelon consumption, with mean systolic blood pressure reduced from 140 mmHg to 120 mmHg (p < 0.05). These findings suggest that watermelon may be an effective dietary intervention for managing hypertension in pregnant women. The implications of the results of this study suggest that watermelon consumption can be considered as part of a strategy to prevent and manage hypertension in maternal health practice, and can be a recommendation for health policy to increase awareness of the importance of a healthy diet during pregnancy.